Investigating the influence of an adjustable zoned air mattress on sleep: a multinight polysomnography study - Wei, Yu; Zhu, Yongpeng; Zhou, Yihan; Yu, Xiaokang; Lin, Huiping; Ruan, Lijun; Lei, Hua; Luo, Yuxi (Frontiers in Neuroscience, 2023)
A comfortable mattress should improve sleep quality. Here, we sought to investigate which sleep parameters could be affected by mattress and the sex difference in such effect. Twenty healthy young adults (ten females and ten males; 22.10±1.25 years) participated in the experiments. A smart adjustable zoned air mattress was designed to maintain comfortable support, and an ordinary mattress for comparison. Participants individually spent four nights on these two mattresses in four orders for polysomnography (PSG) scoring. Sleep architecture, electroencephalogram (EEG) spectrum and heart rate variability (HRV), which respectively reflects the central and autonomic nervous activities, were used to compare the difference between the two mattresses. Individual difference existed in sleep performance. The influence modes of the mattresses were different between the sexes. The adjustable air mattress and the increase in experimental nights both improved the sleep efficiency of females. Males indicated less response to different mattresses. With the increase of the experiment nights, both sexes showed increased REM and decreased N2 proportions, N3 sleep proportion decreased in males, and heart rate decreased in both sexes. The performance of the EEG spectrum supports the above results. In addition, with the adjustable air mattress, the automatic nerve activity during N3 sleep weakened in most participants. Females seem to be more sensitive to mattresses. Experiment night should be related to psychological factors, sexes also indicated some different results for this influence. This study may shed some light on the differences in sleep environment design between the sexes.